Società Dantesca Italiana. Dante on line <http://www.danteonline.it/>, s.i.d. [ma 2000] - Nocita, Teresa (Reti Medievali Rivista, 2001)
Recensione a Società Dantesca Italiana. Dante on line <http://www.danteonline.it/>, s.i.d. [ma 2000]